Low Cost Water Disinfectant System Using Solar Energy - Fatima, Anees; Hany, Omm-e; Shahzad, Atif; Siddiqui, Sara Umair (Journal of Basic & Applied Sciences, 2012)
Solar disinfection unit is unsophisticated, efficient and reasonably priced water treatment process appropriate for use in developing countries. Water was filtered through cloth, net and coconut husk to remove any suspended particles in water which would directly increase the efficiency of solar disinfection. The filtered water is then transferred in solar disinfection unit. Water with Escherichia coli as indicator organism was filled in the solar disinfection unit comprising of four polyethylene terepthalate (PET) plastic bottles joined together with PVC pipes. These bottles were kept in direct sunlight for 12-48 hours. Weather conditions and solar radiation were obtained using different programs. Solar radiations and elevated temperature destroyed the indicator organism efficiently. Health peril of chemical released in water was well thought-out and was determined to be safe with respect to human consumption. The efficiency of solar disinfection was augmented by use of semi-conductor titanium dioxide (TiO2) which reduced the time for exposure up to 90%. The temperature increase and dissolved oxygen decrease in the disinfection process which was overcome by retaining this water in traditional earthenware water storage vessels (mutka). Allowing accessibility to better life through improved quality of water.